PERKEMBANGAN TEKNOLOGI DAN SISTEM INFORMASI UNTUK PENINGKATAN E-GOVERNMENT DALAM PELAYANAN PUBLIK - Wardiningsih, Suprihatmi Sri (Universitas Slamet Riyadi, 2009)
Abstract Growth of information technology in this case computer technology can support the decision making in conducive modern organizations of work in organization can be finished quickly, accurate, and efficient. Information technology (TI) defined by as technology used to obtain get the, manipulation, presenting data. The All manager is this time claimed by their ability to be able to exploit the information influencing organizations so that can make decision precisely pursuant to the information. At our tataran governance recognize the term e-government which is becoming trend in this time, How exploiting TI in governance which we recognize with the phenomenon